Improvement of Dissolution Rate and Bioavailability of Simvastatin Tablet - Dolih Gozali; Taofik Rusdiana; Firman Gustaman (Majalah Farmasetika, 2019)
Simvastatin is used to reduce cholesterol levels via inhibition of the 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase. The low bioavailability in simvastatin is due to the influence of P-glycoprotein, the transporter efflux that plays a role in drug absorption.To increase the bioavailability of simvastatin, it is necessary to add a surfactantwhich serves as a solubilizer and enhancer.The purpose of the study is to determine the effect of Cremophor RH 40 to the dissolution rate and bioavailability improvement of simvastatin tablet. The experiment was consist of four formula with different concentration of Cremophor RH 40 that were 0% (F1), 0,5% (F2), 1%(F3), and 1,5% (F4). Preparation of simvastatin tablets was done by wet granulation method. The tablets obtained were done dissolution test and in vivo test. The formulas with the best value were tested in vivo to the animals. For in vivo study, on the 7th day, the rats blood were taken as Cmax∞ and then the plasma was analyzed with HPLC. Based on the dissolution test results,F2 and F3 gave significant differences (p <0.05) compared to F1. Addition of Cremophor RH 40 of 1% in F3 has the largest simvastatin dissolution rate. The analyze of HPLC on F3 which is the best dissolution result and significant differences was Cmax of F3 (0.3968 ppm). It can be concluded that the addition of Cremophor RH 40 as a surfactant can increase dissolution rate and bioavilability of simvastatin tablet.Keywords: Simvastatin, Cremophor RH 40, Dissolution, HPLC